2016
DOI: 10.1182/blood-2015-09-671172
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the thrombopoietin receptor by mutant calreticulin in CALR-mutant myeloproliferative neoplasms

Abstract: Key Points Mutant CALR induces TPO-independent growth in the human megakaryocytic cell line UT-7/TPO. Mutant CALR binds to the TPO receptor, inducing phosphorylation of JAK2 and activating downstream signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
278
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(307 citation statements)
references
References 25 publications
28
278
1
Order By: Relevance
“…The effect of ruxolitinib on mice with CALR mutations also supports the idea that mutant CALR autonomously activates the JAK-STAT signaling cascade and induces sustained thrombocytosis with increased numbers of megakaryocytes. Our observations, together with previous reports [4][5][6][7], indicate that the CALR mutation is sufficient to augment megakaryocytic cell growth and cause ET, and that CALR mutations, like the JAK2 mutation, play a driver role in MPNs.…”
supporting
confidence: 81%
“…The effect of ruxolitinib on mice with CALR mutations also supports the idea that mutant CALR autonomously activates the JAK-STAT signaling cascade and induces sustained thrombocytosis with increased numbers of megakaryocytes. Our observations, together with previous reports [4][5][6][7], indicate that the CALR mutation is sufficient to augment megakaryocytic cell growth and cause ET, and that CALR mutations, like the JAK2 mutation, play a driver role in MPNs.…”
supporting
confidence: 81%
“…This has been shown to be mediated by direct binding of MPL by the N domain of CALR, a phenomenon that uniquely occurs in the presence of the mutated C-terminus, 48,49 leading to autocrine activation of MPL, JAK2 dimerization and downstream STAT5 and ERK phosphorylation. 46,49 It is therefore clear that the inappropriate activation of JAK2 signaling is common to the three main phenotypic driver mutations (i.e., those in CALR, MPL and JAK2 itself) and plays an important role in disease pathogenesis in each case, in keeping with the clinical efficacy of JAK2 inhibition irrespective of the presence of the mutations in JAK2.…”
Section: Mutations In Mpl and Calrmentioning
confidence: 99%
“…43 Differences in cytosolic calcium mobilization have been reported with the 52 base pair deletion, 44 suggesting that this may be one mechanism by which mutant CALR exerts its effect, and expression of the mutant protein does appear to be particularly restricted to megakaryocytes on immunohistochemical evaluation of bone marrow specimens. 45 More recently, it has been shown that CALR mutations can impart TPO-independence in both cell lines 46,47 and retroviral mouse models, 48,49 in a MPL-and JAK2-dependent manner, mimicking the effect of activating MPL mutations. This has been shown to be mediated by direct binding of MPL by the N domain of CALR, a phenomenon that uniquely occurs in the presence of the mutated C-terminus, 48,49 leading to autocrine activation of MPL, JAK2 dimerization and downstream STAT5 and ERK phosphorylation.…”
Section: Mutations In Mpl and Calrmentioning
confidence: 99%
“…[7][8][9] Furthermore, other key driver mutations associated with ET, affecting thrombopoietin receptor MPL and calreticulin (CALR), also led to increased JAK2 signaling. 10 The JAK1/2 inhibitor, ruxolitinib, was effective in reducing spleen volume, controlling blood counts, and improving symptoms in MF and polycythemia vera (PV) patients. [11][12][13] Ruxolitinib treatment may also result in a survival advantage for patients with MF.…”
Section: Introductionmentioning
confidence: 99%